(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Financial planning forms a basis for the company’s management and determines the company’s objectives; the achievement of these objectives is measured using financial and non-financial indicators. The main budgeting objectives affect the importance of financial and non-financial indicators, thus, contributing to the achievement of the goals. The topicality of the research is determined by the fact that the financial and non-financial indicators have been examined by many authors; however, there exist problems regarding their practical application, since still there is no a consistent approach to the measurement and evaluation of both the financial and non-financial indicators. The study is based on the author's previous theoretical research on the application of financial and non-financial indicators in the evaluation of business performance; as a result, the author has established the sets of financial and non-financial indicators that were used in conducting the practical research.The aim of the current research is to determine the impact of the main company’s budgeting objectives on the evaluation of importance of financial and non-financial indicators on the basis of the opinion survey of Latvian business persons and top-level employees. The Internet survey was used in the research, applying a random sampling method.The research results indicate that the opinions in the groups of respondents regarding the main company’s budgeting objectives differ, and the correlations exist among the main budgeting objectives. Comparison of the impact of the main budgeting objectives on the importance level of the financial and non-financial indicators shows that the possible impact is more significant regarding the importance of the financial rather than non-financial indicators.